2009
DOI: 10.1002/jor.21024
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of sodium channel distribution in the dorsal root ganglion after gradual elongation of rat sciatic nerves

Abstract: To elucidate the pathophysiological mechanisms underlying chronic nerve-stretch injury, we gradually lengthened rat femurs by 15 mm at the rate of 0.5 mm/day (group L, n ¼ 13). The control groups comprised sham-operated (group S, n ¼ 10) and naive (group N, n ¼ 8) rats. Immediately after the lengthening, we performed a conduction study on their sciatic nerves and harvested samples. Electrophysiological and histological analyses showed mild conduction slowing and axonal degeneration of unmyelinated fibers in gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…In support of this finding, the injured DRG and sciatic nerve in this pain model showed reduced Na v 1.7 protein and/or mRNA expression in rodents [45,73,82,83,84]. Na v 1.7 protein expression was also downregulated in trigeminal ganglion of ferrets after trigeminal nerve injury [74]. However, two groups reported a significant increase in Na v 1.7 protein expression in the DRG neurons of rats with painful diabetic neuropathy [56,97], although another study found no change in Na v 1.7 mRNA expression [54].…”
Section: Ttx-sensitive Voltage-gated Sodium Channels and Painsupporting
confidence: 52%
See 1 more Smart Citation
“…In support of this finding, the injured DRG and sciatic nerve in this pain model showed reduced Na v 1.7 protein and/or mRNA expression in rodents [45,73,82,83,84]. Na v 1.7 protein expression was also downregulated in trigeminal ganglion of ferrets after trigeminal nerve injury [74]. However, two groups reported a significant increase in Na v 1.7 protein expression in the DRG neurons of rats with painful diabetic neuropathy [56,97], although another study found no change in Na v 1.7 mRNA expression [54].…”
Section: Ttx-sensitive Voltage-gated Sodium Channels and Painsupporting
confidence: 52%
“…For example, although the immunoreactive expression of Na v 1.3 was found to be upregulated in neuromas from humans [42] and rats [35], little change was observed in neuromas from mice [72]. Moreover, rat studies found no significant change in Na v 1.3 mRNA levels after unilateral sciatic nerve entrapment injury [73] or gradual elongation of sciatic nerve [74]. Downregulation of Na v 1.3 was even reported in the trigeminal ganglia in a ferret model of trigeminal neuropathic pain [75].…”
Section: Ttx-sensitive Voltage-gated Sodium Channels and Painmentioning
confidence: 99%
“…For example, conditions such as epilepsy and pain are due to abnormal regulation of sodium channels by the ubiquitin proteasome system (UPS). [44][45][46][47] A deeper understanding of the molecular mechanisms involved in the UPS mediated degradation of proteins and ion channels may provide novel insights into mechanisms that may alleviate these debilitating diseases. It is important to note, that although there is ample evidence implicating the UPS in neurological diseases, the molecular identity of the ligases and associated proteins remains largely unknown.…”
Section: Trafficking Of Voltage-gated Ion Channelsmentioning
confidence: 99%
“…Kitoh et al, in a study investigating the clinical efficacy of culture-expanded bone marrow cell and platelet-rich plasma injected into patients undergoing tibial and femoral lengthening, demonstrated a decreased healing index, dependent on osteoblastic differentiation of bone marrow cells39 . Ohno et al, in an investigation of the effect of distraction on the rat sciatic nerve, showed slower conduction and axonal degeneration of unmyelinated fibers as well as downregulation of mRNA expression of tetrodotoxin-resistanttype sodium-channel Nav1.8 mRNA in dorsal root ganglion, a finding associated with pain and paresthesia in other studies of neuropathy40 .…”
mentioning
confidence: 94%